Effect of carburizing process in enhancing nickel interlayer adhesion to WC-6% Co-substrate and promoting diamond nucleation and growth - Hassan, A.; Yusof, N.; Izman, S.; Zakiah, K.; Engku, M.; Kurniawan, Denni (Sage, 2016)
Nickel enables nucleation and growth of well-oriented diamond crystals from the small lattice mismatch with diamond. However, its high solubility for carbon results in carbon loss during diamond deposition and, consequently, results in poor nucleation density. In this study, Ni/WC-6%Co specimens were carburized in a high-temperature furnace with inert gas atmosphere in order to provide nickel with sufficient carbon prior to diamond deposition. Two carburizing temperatures (750 C and 850 C) were set for 20 min and 60 min durations. The effect of this process in altering the nickel layer composition was characterized by microscopy, element analysis, and phase identification techniques. Scratch test was performed to evaluate the interface adhesion between the nickel layer and the substrate. The results show that the carburizing process led to the formation of different metallic phases, such as ni ckel carbide and cobalt nickel, which prevented carbon loss during diamond deposition as well as cobalt diffusion into diamond, and thus enhanced diamond nucleation and growth on the nickel surface.